Identificação de padrões de viagens urbanas por meio de análise espacial: estudo de caso de Araraquara, SP - Oliveira, Rafael Augusto de (2024)
Urban mobility has been becoming increasingly important for the operation of cities, currently the greatest expressions of the human organization of life in society. As is related to the access to the various opportunities offered and daily activities in the urban environment, the growing interest in its planning has been consolidating, while its importance and complexity is beginning to be understood. In Brazil, urban mobility planning is the object of Urban Mobility Plans, mandatory for all municipalities with more than 20,000 inhabitants and that also have to elaborate Master Plans. In this context, the city of Araraquara, in the interior of São Paulo, in the process of its Urban Mobility Plan review, had several studies capable of diagnosing the conditions of transport, travels and mobility in its territory. In order to continue these papers, this research aims to apply spatial analysis and spatial statistics techniques to identify and understand patterns related to population travels. Using a Geographic Information System (GIS), a statistical computing environment and a spatial data analysis software, the data collected in the Origin-Destination Survey (O/D) conducted between 2020 and 2021 were used. The analyzes seek to complement previous papers, considering the spatial aspects of income, age, gender, reasons for travel and level of education related to travels using different modes of transportation. The results indicate that the significant distributions of each variable are similar to the distributions of trips as a whole, mostly around the central region and its surroundings, which proves to be a solid urban nucleus. Other secondary and emerging centers are identified in peripheral regions, mainly using alternative modes to the car. In fact, the analyzes can contribute to obtaining additional subsidies for public policies and urban mobility planning in Araraquara.